Pembuatan Aplikasi Augmented Reality Sebagai Media Pembelajaran Penggolongan Obat Berdasarkan Bentuk Sediaannya: Making Augmented Reality Applications As Learning Media Classifying Drugs Based on Their Dosage Forms - Syalom deide Walangitan; Arthur M. Rumagit; Rizal Sengkey (Universitas Sam Ratulangi, 2023)
Abstract - One of its uses is augmented reality technology, which uses a smartphone camera to combine virtual objects in a real environment, so that it can be used in various fields, including as a learning tool. In the field of education, introductory material on the classification of dosage forms can be obtained in college pharmacy courses which discuss each dosage form to broaden the knowledge of each student. In this case the material taught to students still uses traditional books on traditional boards, so that the use of augmented reality technology can be a tool that makes it easier to understand existing forms of medicine in a more modern and interesting way. Therefore, researchers want to research the topic, namely augmented reality as a learning medium for classifying drugs based on their dosage forms by designing drug forms with Unity, Blender 3D and Vuforia developers to display drug forms in 3D object forms with target images, with the smartphone camera pointed at the marker. This application uses the MDLC (Multimedia Development Life Cycle) methodology which includes several stages, namely concept, design, material collecting, assembly, testing and distribution. This application runs on the Android platform. Based on the results of questions and answers with 31 respondents, 100% stated that this application can help understand information about drug classification based on its dosage form in a more interesting way. Keywords: Augmented Reality, Multimedia Development Life Cycle, Drug dosage forms, Applications, image targets, 3D objects, Android. Abstrak - Salah satu penggunaannya adalah teknologi augmented reality, yang menggunakan kamera smartphone untuk menggabungkan objek virtual dalam lingkungan nyata, sehingga dapat digunakan di berbagai bidang, termasuk sebagai alat pembelajaran. Dalam bidang pendidikan, materi penggolongan bentuk sediaan obat dapat diperoleh pada pembelajran di SMK jurusan farmasi yang membahas masing-masing bentuk sediaan obat untuk memperluas pengetahuan setiap siswa. Dalam hal ini materi yang diajarkan kepada siswa menggunakan buku dan papan tulis yang sifatnya konvensional, sehingga penggunaan teknologi augmented reality dapat menjadi alat yang mempermudah proses belajar dalam memahami bentuk sediaan obat yang ada dengan cara yang lebih menarik dan modern. Oleh karena itu peneliti ingin melakukan penelitian dengan topik yaitu augmented reality sebagai media pembelajaran penggolongan obat berdasarkan bentuk sediaannya dengan perancangannya menggunakan developer Unity, Blender 3D dan Vuforia untuk menampilkan bentuk obat dalam bentuk objek 3D dengan gambar target, dengan kamera smartphone diarahkan ke penanda. Aplikasi ini menggunakan metodologi MDLC (Multimedia Development Life Cycle) yang meliputi beberapa tahapan yaitu concept, design, material collecting, assembly, testing dan distribution. Aplikasi ini berjalan pada platform Android. Berdasarkan hasil tanya jawab dengan 31 responden, 100% menyatakan bahwa aplikasi ini dapat membantu memahami tentang informasi penggolongan obat berdasarkan bentuk sediaannya dengan cara yang lebih menarik. Kata Kunci: Augmented Reality, Multimedia Development Life Cycle, Bentuk sediaan obat, Aplikasi, image target, objek 3D, Android.